A high-selectivity double-mode SIW bandpass filter utilizing the modified parallel coupled microstrip lines. Issue 4 (19th May 2021) - Yin, Bo; Huang, Qianqian; Hao, Hongang; Zhang, Hongsheng
ABSTRACT: In this article, a high-selectivity double-mode substrate integration waveguide bandpass filter utilizing modified parallel coupled microstrip lines (MPCML) is presented. The designed method is analyzed in detail. Six metal vias are designed to perturb TE-101 mode and TE-103 mode. The resonant frequency of the perturbed TE-101 mode is shifted to high frequency, close to that of TE-102 mode, which caused the formation of passband. The resonant frequency of the perturbed TE-103 mode is shifted to high frequency, improving out-of-band performance. Simultaneously, the coplanar waveguide structure is used to adjust the external quality factor. Two rectangular slotlines are introduced to adjust center frequency and bandwidth slightly. Two rectangular stubs are designed for better source and load matching. Three transmission zeros (TZs) are obtained to improve the selectivity. The designed MPCML promotes the generation of TZs. Another TZ is obtained by the coupling between TE-102 mode and TE-103 mode. The designed filter operates at 14.4 GHz with bandwidth of 800 MHz. The measured return loss is better than 15 dB, and the minimum insertion loss is 1.60 dB. The measurement is agreed with the simulation.